Achieving ambipolar vertical organic transistors via nanoscale interface modification - Li, Sheng-Han; Xu, Zheng; Ma, Liping; Chu, Chih-Wei; Yang, Yang (Applied physics letters, 2007)
Organic field-effect transistors have been the subject of much recent inquiry due to their unique properties. Here, the authors report an ambipolar vertical organic field-effect transistor, which consists of a capacitor cell vertically stacked with an organic active cell, separated by a thin source electrode. By inserting a nanoscale transition-metal-oxide layer at the source/organic interface, the authors fabricated the organic ambipolar transistors with low working voltage and high current output. The thin transition-metal oxide and partial oxidization metal grains form a unique nanostructure that balances the injection barrier height of two types of carriers at the source/organic contact.